2023
DOI: 10.1039/d2ta09698f
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated MXenes accelerate the hydrogen evolution activity of in situ induced snowflake-like nano-Pt

Abstract: The development of water electrolysis hydrogen production technology is related to the process of large-scale application of green energy, but the high cost of Pt based materials with high catalytic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Organic intercalates include polar organic molecules and large organic base molecules, while ionic aqueous solution intercalates include metal hydroxides or halide salts suitable for delaminating large surfaces. 127,128 For example, Shekhirev et al demonstrated how the delamination of multilayer MXene into individual nanosheets considerably impacts the lateral size of the resulting flakes, creating an effective delamination method that keeps flake size intact and prevents fracturing. Figures 4a-4d illustrates the size distribution of MAX particles.…”
Section: Synthesis and Characterization Of Mxene Hybrid Compositesmentioning
confidence: 99%
“…Organic intercalates include polar organic molecules and large organic base molecules, while ionic aqueous solution intercalates include metal hydroxides or halide salts suitable for delaminating large surfaces. 127,128 For example, Shekhirev et al demonstrated how the delamination of multilayer MXene into individual nanosheets considerably impacts the lateral size of the resulting flakes, creating an effective delamination method that keeps flake size intact and prevents fracturing. Figures 4a-4d illustrates the size distribution of MAX particles.…”
Section: Synthesis and Characterization Of Mxene Hybrid Compositesmentioning
confidence: 99%
“…Loading Pt nanoparticles onto carbon-based materials has greatly improved the MA of Pt, for example, hollow mesoporous carbon spheres, 11 defective graphene, 12,13 and nitrogen-doped carbon materials. 14,15 Metal oxides, metal sulfides, metal carbides, and metal selenides are also used as functional carriers, such as MnO 2 , 16 WO 3−x , 17,18 F-doped SnO 2 , 19 TiO 2 -O V , 20 TiB x O y , 21 MoS 3 , 22 VS 2 , 23 WC x , 24,25 Mo 2 C, 26 MXene, [27][28][29] and CdSe, 30 which further enhance the activity and stability of HER. In addition, the trace Pt combined with other transition metals has also exhibited definite HER activity, such as CoPt-Pt SA , 31 Pt/Ni-Mo-N-O, 32 PtNi, 33 PtRu, 34,35 PtW, 36 Pt@Pd 3 Pb, 37 PtPd, 38 PtPdRuTe, 39 and PtSe 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical water splitting includes the hydrogen evolution reaction (HER) with two-electron transfer at the cathode and the oxygen evolution reaction (OER) with four-electron transfer at the anode in the electrocatalytic system. In the PEMWE electrolyzer, the HER is usually catalyzed by highly efficient platinum, which is easily realized. However, the acid OER required in PEMWE shows inherently sluggish kinetics with multiple reaction steps and involves complicated intermediates such as the formation of *OH through breaking the strong covalent OH–H bond, dominating the overpotential of the PEMWE electrolyzer. Additionally, most OER catalysts are difficult to keep long durability in acid, owing to the strong oxidation at high operation voltages. , Currently, the commercial OER catalyst is limited to iridium-based materials ($1238 m –2 ) due to their balanced activity and stability in acidic electrolytes. Unfortunately, the application domain of iridium-based catalysts is impeded by the extremely rare reserve of iridium (0.001 ppm in the Earth’s crust) and low annual global production (less than 9 tons), along with the need of more efficient and stable OER electrocatalysts (DOE target: 80,000 h and $150/kW for PEMWE system over longer-term developments). In fact, the cost of Ru is from 1/5 to 1/16 of Ir metal, and Ru-based electrocatalysts exhibit better OER performance compared to Ir-based ones, benefiting from the suitable binding strength between reaction intermediates and surface active sites. As we know, the efficient Ru metal or RuO 2 exhibits relatively low durability due to the formation of dissolvable RuO 4 derivatives by overoxidation in electrolytes. , In this perspective, substantial efforts have been dedicated to further improving the electrocatalytic OER performance and stability of Ru-based electrocatalysts. , Despite several existing reviews on Ru-based OER electrocatalysts, ,,,, there is still a lack of specialized and critical reviews specifically focusing on water oxidation in acid, encompassing both experimental and theoretical research progress on Ru-based electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%